High performance solid-state PbS/CuS hetero-nanostructured quantum dots-sensitized solar cells - Kwon, O. Hoon; Heo, Jin Hyuck; Park, Soowung; Kim, Sang Wook; Im, Sang Hyuk (Journal of Industrial and Engineering Chemistry, 2019)
PbS/CuS hetero-nanostructured (HNS) quantum dots(QDs) with finely controlled PbS core-size (˜3, ˜5, and ˜7 nm) and CuS content (4, 7, 11, 14, 17, and 45 mol%) were successfully synthesized via the suppressed cationic exchange reaction rate by reducing the reaction temperature down to −3 °C. By the precise synthesis of the PbS/CuS HNS QDs, we found that the PbS/CuS HNS QDs with ˜3 nm in core-size and 14 mol% CuS have the most effective charge separation/injection from the HNS QDs to the mesoscopic TiO 2 electron conductor, thereby the sensitized solar cells exhibited high power conversion efficiency of 9.3%.
Keywords: Cationic exchange; Cationic exchange reactions; Effective charge; Hetero-nanostructures; High power conversion; Nanostructured quantum dots; Reaction temperature; Sensitized solar cells; Cationic exchange; CuS; Hetero-nanostructure; PbS; Quantum dots; Solar cells